Book Review: School Leadership for Authentic Family and Community Partnerships:Research for Transforming Practice - Hal A. Lawson (Journal of Research in Rural Education, 2012)
The dominant model for school improvement can be characterized briefly as follows. Teams of educators with hand-picked parents and other community members decide which priorities their respective schools will emphasize. Typically, these priorities are bracketed by the regular school day and fall within the school's boundaries. The dominant model, thus, can be described as "walled-in," buildingcentered, and professionally-controlled (Lawson, 2010a).